An Analysis of Teacher’s Speech Acts in Teaching and Learning Process - Widi Andewi; Winia Waziana (TEKNOSASTIK, 2019)
This research focuses on classroom interaction during teaching and learning process that included investigation of types and functions of the speech acts produced by teacher. It was designed as a qualitative research. The subject of this research was an English teacher in SMAN 1 Kalirejo. The data were collected through recording. The data were analyzed through three cyclical steps: data reduction, data display, and conclusion drawing or verification. The results show that directives speech acts is mostly produced by the teacher than the other speech acts. This can be seen from the data that 33 utterances (21.2%) are representative speech acts, 6 utterances (3.8%) as expressive speech acts, 112 utterances (71.8%) as directives speech acts, and 5 utterances (3.2%) as commisive speech acts. The types and functions of directives speech acts proposed are need statement, bald imperative, embedded imperative, permission directive, and question directive.